Framing of Covid-19 Vaccine News on CNN Website: A Discourse Analysis - Muhammad Luhfi; Ansor Putra; Arman Arman (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2021)
This study is intended to analyze the form of Framing of Covid-19 vaccine new on CNN website based on Discourse Analysis perspective theory of Framing Analysis by Zhondang Pan & Gerald M. Kosicki. The objective of this research is â€œTo describe how are the forms of framing of covid 19 vaccine news on CNN websiteâ€. This research used the descriptive qualitative method. The researcher used Zhondang Pan & Gerald M. Kosicki Framing Models to analyze the data. The source of the data in this research was taken from News on CNN Website. The data was collected through reading intensively, identifying and selecting, classifying, describing, and interpreting the data to get a complete conclusion of Framing Covid-19 Vaccine News on CNN Website by Zhondang Pan & Gerald M. Kosicki theory. The researcher analyzes six pieces of data or news from the CNN website. The result showed there are framing the researcher found based on four models of framing Pan & Kosicki namely: Syntactical Structure, Script Structure, Thematical Structure and Rhetorical Structure in six data or news from CNN website.